PENANAMAN NILAI-NILAI BUDAYA ISLAM MELALUI PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTs MUHAMMADIYAH PATIKRAJA - Annisa, Aulia; Sulaeman, Ahmad (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
The rapid development of the era and technology has impacted the moral and cultural degradation of Indonesian society, particularly among Muslims. Value education is expected to be a solution in facing the swift flow of information in a fast-moving information environment in modern times. The aim of this research is to understand and describe the methods used in instilling Islamic cultural values at MTs Muhammadiyah Patikraja, as well as the resulting impacts. This research uses a qualitative approach, employing observation and interviews as data collection techniques. The findings of this study indicate that the teaching of Islamic cultural values through the understanding of Islamic history is conducted in stages using learning strategies and media tailored to the conditions and needs of the students. Positive changes in students' attitudes and actions in their daily lives demonstrate the impact of the formation of Islamic cultural values.